Excellent outcome of minimal residual disease-defined low-risk patients is sustained with more than 10 years follow-up: results of UK paediatric acute lymphoblastic leukaemia trials 1997–2003. Issue 5 (10th February 2016) - Bartram, Jack; Wade, Rachel; Vora, Ajay; Hancock, Jeremy; Mitchell, Chris; Kinsey, Sally; Steward, Colin; Moppett, John; Goulden, Nick
Abstract : Background: Minimal residual disease (MRD) is defined as the presence of sub-microscopic levels of leukaemia. Measurement of MRD from bone marrow at the end of induction chemotherapy (day 28) for childhood acute lymphoblastic leukaemia (ALL) can highlight a large group of patients (>40%) with an excellent (>90%) short-term event-free survival (EFS). However, follow-up in recent published trials is relatively short, raising concerns about using this result to infer the safety of further therapy reduction in the future. Methods: We examined MRD data on 225 patients treated on one of three UKALL trials between 1997 and 2003 to assess the long-term (>10 years follow-up) outcome of those patients who had low-risk MRD (<0.01%) at day 28. Results: Our pilot data define a cohort of 53% of children with MRD <0.01% at day 28 who have an EFS of 91% and long-term overall survival of 97%. Of 120 patients with day-28 MRD <0.01% and extended follow-up, there was one death due to treatment-related toxicity, one infectious death while in complete remission, and four relapse deaths. Conclusions: The excellent outcome for childhood ALL in patients with MRD <0.01% after induction chemotherapy is sustained for more than 10 years from diagnosis. This supports the potential exploration of further reduction of therapy in this group, in an attempt to reduce treatment-related mortality and late effects.